A method to screen T lymphocyte epitopes after oral immunisation of humans: application to cholera toxin B subunit - Castello-Branco, Luiz R.R.; Griffin, George E.; Dougan, Gordon; Lewis, David J.M. (Vaccine, 1995)
The response to oral immunisation of humans with classical biotype cholera toxin B subunit was studied to identify immunodominant T lymphocyte determinants. The in vitro proliferative response to pools of 12-mer peptides and larger peptides used individually was analysed by a novel statistical approach, and identified an immunodominant region in residues 70–79 in immunised subjects, when either pools or individual peptides were employed. In contrast, a patient infected with El Tor biotype had a dominant response to residues 40–60. The statistical software employed in this study may enable efficient screening of antigens for immunodominant T lymphocyte determinants when blood precursor frequencies are low following immunisation, and may therefore be of special relevance to mucosal vaccines.